Do the Banks Comply to GRI guidelines for Sustainable Reporting Practices? Empirical Evidence from Bangladesh - Biswas, Tanmay; Moudud-Ul-Huq, Syed; Chakraborty, Brishti; Lima, Reshma Pervin; Jahan, Shakila (Society & Sustainability, 2020)
This paper explores the degree and nature of sustainability reporting practices of listed banks in Bangladesh in compliance with the Global Reporting Initiative (GRI) guidelines. Data are gathered from annual reports through content analysis of 29 banks listed in the Dhaka Stock Exchange (DSE) and Chittagong Stock Exchange (CSE) for the period between 2011 and 2018. Stakeholder and legitimacy theory is the theoretical perspectives underlying the study. The findings of the study revealed that 0% in 2011 and 17.14% in 2018 disclosed sustainability reports in line with GRI. On the other hand, the disclosure of sustainability information trend has increased from 32% in 2011 to 59% in 2018 considering 22 categories of information where most of the banks disclosed the highest information relating to green banking (C7) least information relating to public policy (C19). The major limitations of the study are the size of the sample, only secondary sources of data, and the use of descriptive statistics. The policymakers (Bangladesh Bank, Ministry of finance, commerce, law, and environment), management of the respective organizations, the NGOs, and professional accounting bodies can progress to enact and amend corporate laws for effective sustainability reporting for the public and private entities. This research recognizes the gap of sustainable reporting practices to implement the vision of ‘5 Ps’ (people, prosperity, partnership, peace, and the planet) according to UN Sustainable Development Goals (SDGs) 2030.